Core transport barriers induced by fast ions in global gyrokinetic GENE simulations. (1st June 2022) - Di Siena, A; Bilato, R; Görler, T; Poli, E; Bañón Navarro, A; Jarema, D; Jenko, F
Abstract: A novel type of internal transport barrier called F-ATB (fast ion-induced anomalous transport barrier) has been recently observed in state-of-the-art global gyrokinetic simulations on a properly optimized ASDEX Upgrade experiment and presented in Di Siena et al (2021 Phys. Rev. Lett. 127 025002). Unlike the transport barriers previously reported in the literature, the trigger mechanism for the F-ATB has been shown to be a wave-particle resonant interaction between supra-thermal particles—generated via ion cyclotron resonance heating—and ion scale plasma turbulence. This resonant mechanism strongly depends on the particular shape of the fast ion temperature and density profiles. Therefore, to further improve our theoretical understanding of this transport barrier, we present results exploring the parameter space and physical conditions for the F-ATB generation by performing a systematic study with global GENE simulations. Particular emphasis is given to the transport barrier width and its localization by scanning over different energetic particle temperature profiles. The latter are varied in amplitude, half-width, and radial localization of an ad-hoc Gaussian-like energetic particle logarithmic temperature gradient profile. For the reference parameters at hand, a threshold in the ratio between the fast ion and electron temperature and the amplitude of the fast ion logarithmic temperature gradient is identified to trigger the transport barrier effectively. The role of q = 1 rational surface to the transport barrier formation is investigated as well by retaining electromagnetic effects and its impact found to be negligible for this particular barrier formation mechanism.